Fully noncontact nonlinear ultrasonic characterization of thermal damage in concrete and correlation with microscopic evidence of material cracking. (September 2019) - Yang, Chenglong; Chen, Jun
Abstract: This paper investigates the degradation of concrete integrity under the rising temperature using a nonlinear ultrasonic second harmonic generation (SHG) technique based on a fully non-contact approach. The microscopic cracks accumulated during the course of thermal damage is then analytically and experimentally quantified by the elastic wave velocity inversion method and X-ray computed tomography (CT) technique, respectively. The nonlinear parameter calculated by the non-contact SHG technique not only shows a higher sensitivity to the damage growth than traditional macroscopic ultrasonic parameter such as wave velocity, but also presents an excellent correlation with microscopic quantified crack density by showing a proportionally increase with the propagation distance of ultrasonic waves. The experimental findings in this work indicate that the non-contact SHG technique can truly reveal the progressive microscopic cracking of concrete through the macroscopic nondestructive measurements and is suitable for the assessment of globally distributed damage with a high sensitivity and reliability.